Transaction taxes, traders' behavior and exchange rate risks - Markus Demary (Kiel University, Department of Economics, 2006)
We propose a new model of chartist-fundamentalist-interaction in which both groups of traders are allowed to select endogenously between different forecasting models and different investment horizons. Stochastic interest rates in both countries and different behavioral assumptions for trend-extrapolating and fundamental based forecasts determine the agents' market orders which drive the exchange rate. A numerical analysis of the model shows that it is able to replicate stylized facts of observed financial return time series like excess kurtosis and volatility clustering. Within this framework we study the effects of transaction taxes on exchange rate volatility and traders' behavior measured by their population fractions. Simula- tions yield the result that on the macroscopic level these taxes reduce the variance of exchange rate returns, but also increase their kurtosis. Moreover, on the microscopic level the tax harms short-term speculation in favor of long-term investment, while it also harms trading rules based on economic fundamentals in favor to trend extrapolating trading rules.
Keywords: 330; Chartist-Fundamentalist-Interaction; Exchange Rates; Financial Market Volatility; Transaction Taxes; Devisenhandel; Wertpapieranalyse; Devisenmarkt; Mikrostrukturanalyse; Tobinsteuer; Wirtschaftspolitische Wirkungsanalyse; Wechselkursrisiko; Theorie